SEJARAH KONVERSI DARI ANIMISME KE AGAMA ISLAM SUKU ANAK DALAM DI KABUPATEN SAROLANGUN PROVINSI JAMBI (2005-2013) - Muhammad Ahat; Arki Auliahadi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
Bukit Duabelas is in the central part of Jambi Province between land transportation routes, namely between the central and eastern crossings of Sumatra, and the central crossing of Jambi. The position of Bukit Duabelas is also located among four sizable rivers, namely; Batang Hari River is in the north, Tabir River is in the west, Tembesi River is in the east and Merangin River is in the south. Ethnic, ethnic and religious cultures also influence communication styles, so culture can become an obstacle in integrating with one another, cultural barriers in integrating are caused by differences in norms and values shared by those involved in communicating. Suku Anak Dalam is one of the Remote Indigenous Communities that inhabits the interior of Jambi Province, such as those in Merangin and Sarolangun Regencies. Since the last 8 years the Remote Indigenous Communities or better known as Suku Anak Dalam, have begun to experience social changes in the way they dress, education and religion. The Anak Dalam tribe has also begun to adapt to the outside community (Village People). Lately, many Anak Dalam tribes have gradually abandoned their ancestral beliefs and converted to Islam.